PENGARUH ALOKASI DANA DESA DAN PENGELOLAAN DANA DESA TERHADAP KINERJA KEPALA DESA BERIMPLIKASI PADA KESEJAHTERAAN MASYARAKAT (Studi di Kecamatan Samalanga Kabupaten Bireuen) - Rizal, Muhammad; Endang; Sri (LPPM-UNIKI, 2024)
This research tries to analyze empirically: the influence of village fund allocation and Village Fund management in villages in Samalanga District on the performance of village heads. As well as its relationship with community welfare. Using a number of community samples as sources, through questionnaires. With a quantitative path analysis approach. The research results show: (1) Village Fund Allocation is related to village fund management. (2) Village fund allocation affects the performance of the Village Head by 18.13%. (3) Village Fund Management influences Village Head Performance by 22.05%. (3) Simultaneously the allocation of village funds and management of village funds makes a significant contribution to the performance of the Village Head by 64.2%. (4) There is an influence of the Village Head's performance on the welfare of the village community by 55.8%. (5) There is a direct and indirect influence of village fund allocation on community welfare in the village of Samalanga District, Bireuen Regency, namely 19.82%, there is also a direct and indirect influence of village fund management on community welfare. the community in Samalanga Village, Samalanga District is 23.03%.